AESTHETICS SENSIBILITY: DEBATING THE NATIONAL CURRICULUM GUIDELINES FOR REGULAR HIGH SCHOOL - Batista, Luciana Lima; Cintra, Wagner [UNESP] (Centro Univ Nove Julho, 2015)
This work intends to debate subjects about the national curriculum guidelines for regular high school regarding aspects about the guiding principles, emphasizing the principle of aesthetics sensibility. In this context it is intended to explain the conceptual understandings about the purpose of secondary education and the importance of aesthetic experience to this formation.
Keywords: High school; Education; Aesthetics